The Use of Information and Communication Technology-based Science Resources by New South Wales Stage 3 Primary School Teachers - Galvin, Anne Therese (Curtin University, 2017)
The use of Information and Communication Technology-based science resources by selected teachers of Stage 3 students across New South Wales schools to enhance their science content knowledge was investigated. An Interpretivist epistemology informed a mixed research methodology. Results indicated that the teachers did not engage with these resources to any substantial degree and confirmed science’s generally low subject status. Preparations for high-stakes testing are negatively impacting science-teaching. Teacher-participation rates in professional learning activities were low.